New insights into the brain involvement in patients with Crohn's disease: a voxel‐based morphometry study. Issue 2 (23rd September 2012) - Agostini, A.; Benuzzi, F.; Filippini, N.; Bertani, A.; Scarcelli, A.; Farinelli, V.; Marchetta, C.; Calabrese, C.; Rizzello, F.; Gionchetti, P.; Ercolani, M.; Campieri, M.; et al.
Abstract Background Crohn's disease (CD) is a chronic intestinal disorder characterized by overproduction of inflammatory cytokines and recurrent abdominal pain. Recently, brain morphological abnormalities in the pain matrix were found in patients with chronic pain disorders including irritable bowel syndrome. To investigate potential structural brain changes associated with CD, we used magnetic resonance imaging (MRI). Furthermore, we tested whether in patients gray matter (GM) volumes correlated with disease duration. Methods Eighteen CD patients in remission and 18 healthy controls underwent structural MRI. Voxel‐based morphometry (VBM) is a fully automated technique allowing identification of regional differences in the amount of GM enabling an objective analysis of the whole brain between groups of subjects. VBM was used for comparisons and correlation analysis. Key Results With respect to controls, CD patients exhibited decreased GM volumes in portion of the frontal cortex and in the anterior midcingulate cortex. Disease duration was negatively correlated with GM volumes of several brain regions including neocortical and limbic areas. Conclusions & Inferences Crohn's disease is associated with brain morphological changes in cortical and subcortical structures involved in nociception, emotional, and cognitive processes. Our findings provide new insight into the brain involvement in chronic inflammatory bowel disorders.